2014
DOI: 10.1016/j.engfracmech.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Constraint analysis of defects in strength mismatched girth welds of (pressurized) pipe and Curved Wide Plate tensile test specimens

Abstract: Please cite this article as: Verstraete, M.A., De Waele, W., Denys, R.M., Van Minnebruggen, K., Hertelé, S., Constraint analysis of defects in strength mismatched girth welds of (pressurized) pipe and curved wide plate tensile test specimens, Engineering Fracture Mechanics (2014), doi: http://dx.doi.org/10. 1016/j.engfracmech.2014.07.018 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Therefore, it is unrealistic to conduct a large number of tests accounting for all these factors, and the method of combining numerical simulations and experiments has become a good auxiliary research method. Hertel e et al (Hertel e et al, 2013(Hertel e et al, , 2014Verstraete et al, 2014), confirmed that the CWP specimens seem to be a good representative of the constraints in pipe specimens in the case of mismatched welding. They performed a large series of finite element analysis (FEA) simulations and tests of CWPs to quantify the effect of pipe steel heterogeneity on strain capacity and proposed a new strain capacity equation.…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, it is unrealistic to conduct a large number of tests accounting for all these factors, and the method of combining numerical simulations and experiments has become a good auxiliary research method. Hertel e et al (Hertel e et al, 2013(Hertel e et al, , 2014Verstraete et al, 2014), confirmed that the CWP specimens seem to be a good representative of the constraints in pipe specimens in the case of mismatched welding. They performed a large series of finite element analysis (FEA) simulations and tests of CWPs to quantify the effect of pipe steel heterogeneity on strain capacity and proposed a new strain capacity equation.…”
Section: Introductionmentioning
confidence: 83%
“…In literature, several (numerical) studies indicate that the constraint in SENT specimens is comparable to pipe specimens [14,50]. Additionally considering the previously published correspondence in constraint between pipe and wide plate specimens [17], it was therefore expected for wide plate and SENT specimens to experience a similar constraint. A closer look to the published literature on SENT testing shows however that the correspondence in constraint is primarily observed for (extremely) shallow notch depths (typically a 0 /W = 0.1).…”
Section: Discussionmentioning
confidence: 99%
“…For the welded specimens, the initial notch has been located at the weld metal center (WMC) line. Since the relative crack depth range of R-curve scatter band in terms of CTOD is known to significantly alter the constraint both in CWP and SENT tests [17,20,21], specimens of nominally equal crack depth are compared. Focusing on the medium scale tests, so-called medium wide plate (MWP) specimens with a reduced width of 150 mm were selected over the traditionally considered 300 mm wide Curved Wide Plate (CWP) specimens.…”
Section: Test Specimens and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation